2013
DOI: 10.1177/1753425912474851
|View full text |Cite
|
Sign up to set email alerts
|

A TLR4-interacting SPA4 peptide inhibits LPS-induced lung inflammation

Abstract: The interaction between surfactant protein-A (SP-A) and TLR4 is important for host defense. We have recently identified an SPA4 peptide region from the interface of SP-A-TLR4 complex. Here, we studied the involvement of the SPA4 peptide region in SP-A-TLR4 interaction using a two-hybrid system, and biological effects of SPA4 peptide in cell systems and a mouse model. HEK293 cells were transfected with plasmid DNAs encoding SP-A or a SP-A-mutant lacking SPA4 peptide region and TLR4. Luciferase activity was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 54 publications
3
52
0
Order By: Relevance
“…Mouse bone marrow-derived JAWSII dendritic cells (1 3 10 6 cells) were transfected with 2 mg of each plasmid construct encoding WTTLR4 or TLR4DN (Pro at position 712 substituted with His), using TransIT-TKO transfection reagent (Mirus Bio, Madison, WI, USA) per the previously published method [16,19]. The plasmid DNA constructs were obtained from Dr. Lynn Hajjar (University of Washington, Seattle, WA, USA).…”
Section: Cell Culture Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mouse bone marrow-derived JAWSII dendritic cells (1 3 10 6 cells) were transfected with 2 mg of each plasmid construct encoding WTTLR4 or TLR4DN (Pro at position 712 substituted with His), using TransIT-TKO transfection reagent (Mirus Bio, Madison, WI, USA) per the previously published method [16,19]. The plasmid DNA constructs were obtained from Dr. Lynn Hajjar (University of Washington, Seattle, WA, USA).…”
Section: Cell Culture Systemsmentioning
confidence: 99%
“…Furthermore, upon treatment of LPS-and ATP-challenged cells with SPA4 peptide, the mRNA and cellular protein levels of NLRP3 and pro-IL-1b, NLRP3 inflammasome formation, caspase activity, and secreted levels of IL-1b are significantly reduced. Together, our results indicate that the suppression of LPS-TLR4 signaling by SPA4 peptide [14][15][16] further reduces the NLRP3 inflammasome and alleviates inflammatory response.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In both cases, exogenous given SP-A led to "rescue" of the innate and adaptive immune phenotypes observed in SP-A-deficient mice (134)(135)(136)(137). More recently, Awasthi and colleagues has found that a specific fragment of SP-A (20-mer) has the ability to inhibit LPS-induced cytokine production and lung inflammation by interaction with TLR-4 (138). This finding suggests the possibility of other SP-A fragments that may be active against a specific receptor target for which SP-A is known to associate, such as TLR-2, SIRP-a, and CD91.…”
Section: Possibility Of Therapeutic Surfactants In Eosinophilic Diseasesmentioning
confidence: 99%
“…TLR4 on platelets recognizes PAMPs of pathogens specifically LPS of gram negative bacteria. These receptors also recognize endogenous DAMPs which include heat shock proteins and fibronectin [21] . Platelets are further able to present microorganisms to neutrophils other immune cells, activating a portion of the innate immune system.…”
Section: Cascade Response To Severe Sepsismentioning
confidence: 99%